COLLECTIVE RIGHTS AND ACCESS TO JUSTICE: DIFFICULTIES AND POSSIBILITIES IN THEIR PROCEDURAL TREATMENT FROM A CITIZENSHIP PERSPECTIVE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
In an effort to relate discussions involving collective rights and access to justice, this paper strives to understand them from a citizens' perspective. There are difficulties, but also possibilities in this relationship, and the effort of this text is to explain them. By emphasizing the importance of the discussions, we highlight not only the difficulties but also the possibilities that collective procedural treatment offers. However, it is not a panacea: although it is not impotent, it is not omnipotent. However, we are not looking for anomie or an impossibility of answers. In fact, the aim is to raise greater and better possibilities for answers with questions that are susceptible to regular intersubjective and rational control.We used deductive method based on a literature review.